Efficacy of Oroxylin A in ameliorating renal fibrosis with emphasis on Sirt1 activation and TGF-β/Smad3 pathway modulation - Li, Guangzhuang; Xian, Sentao; Cheng, Xianchao; Hou, Yunhua; Jia, Wenqing; Ma, Yukui (Frontiers in Pharmacology, 2024)
Introduction Renal fibrosis poses a serious threat to human health. At present, there are few types of traditional Chinese medicine used to treat this disease, and Oroxylin A (OA), as a natural product with multiple biological activities, is expected to be used for the treatment of renal fibrosis. Methods The tolerance of osteoarthritis and its impact on renal fibrosis were studied through ADMET, Lipinski’s filter, establishment of a unilateral ureteral obstruction (UUO) model, and molecular docking. Results OA has good drug tolerance. Compared with the sham group, UUO mice that did not receive OA treatment showed severe tubular dilation and atrophy, extracellular matrix (ECM) deposition, and inflammatory cell infiltration in their kidneys, while OA-treated mice showed significant improvement in these symptoms. OA treatment remarkably restrained the accumulation of fibronectin and α-SMA. Moreover, OA treatment remarkably decreased the abnormal upregulation of inflammatory factors (IL-1β, IL-6, and TNF-α) in the obstructed kidney of UUO mice. Sirtuin1 (Sirt1) expression was markedly diminished in the kidneys of UUO mice and TGF-β1-induced HK-2 cells, whereas this reduction was largely reversed after OA treatment. The results support that OA exerts antifibrotic effects partly through the promotion of the activity of Sirt1. In in vitro results, OA treatment markedly inhibited the activation of Smad3 in UUO mice, thereby ameliorating renal fibrosis. OA could form hydrogen bonds with key the amino acid ASN226 in Sirt1, thereby activating Sirt1, which might also be the reason why OA could resist renal fibrosis. Discussion Our study indicated that OA might exert anti-renal fibrosis effects through the activation of Sirt1 and the suppression of the TGF-β/Smad3 signaling pathway.